Edukasi Isi Piringku Sebagai Upaya Pencegahan Anemia Pada Ibu Hamil - Tutik Ekasari (CV. Multi Kreasi Media, 2025)
Anemia in pregnancy is a condition where the hemoglobin (Hb) level in the blood is less than normal and the hemoglobin (Hb) level in the mother decreases from the normal Hb level, which is <11 g / dL. Anemia that often occurs in pregnancy is iron deficiency anemia which is referred to as a